IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING HORTATORY EXPOSITION TEXTS THROUGH DICTOGLOSS TECHNIQUE - Nova Susanti and Lidiman S.M. Sinaga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2012)
This research attempts to improve students’ achievement in writing hortatory exposition text by using Dictogloss Technique. The result showed the improvement of students’ achievement in writing hortatory exposition text. It was found that the mean of the students’ scores in every test was improved. In the first test, the mean was 38.7 and there was 2.3% of the students who got up 75 points (Minimum Completeness Criteria), in the second test, it was 65.1 and 19.04% of the students who got up 75 points, and in the last one, the mean was 79.4 and there was 73.8% of the students who got up 75 points. The students felt enthusiastic, enjoyable, and active in teaching learning process through Dictogloss Technique. The result of the research showed the progress of achievement scores, it can be concluded that Dictogloss Technique gives contribution to improve students’ achievement in writing hortatory exposition text. Keywords: Achievement, Writing, Hortatory Exposition Text, Dictogloss Technique